Contemporary Fiqh in Indonesia: The Dynamics of Istinbat al-Aḥkām at Ma'had Aly Salafiyah Shafi'iyah Sukorejo Situbondo - Sulthon, M.; Syafi'i, Imam; Nizami, Auliya Ghazna (Universitas Islam Negeri Jakarta, 2024)
Fatwas have so far been issued by religious institutions in Indonesia. Not many Islamic educational institutions based in pesantren perform istinbath al-ahkam in response to contemporary issues. Ma'had Aly Salafiyah Syafi'iyah Sukorejo Situbondo in East Java (Ma'had Aly Situbondo) is one of the Islamic educational institutions within the pesantren environment contributing to the formulation of fatwas. This research examines the istinbāṭ al-ahkām conducted by Ma'had Aly Situbondo using a field research method involving interviews with students and lecturers of Ma'had Aly Situbondo, as well as studying documents from the Tanwirul Afkar bulletin from 2020-2021. The bulletin contains a collection of findings from the Istinbāṭ al-Ahkām Ma'had Aly Situbondo addressing contemporary legal issues. The research findings explain that istinbāṭ al-ahkām at Ma'had Aly Situbondo uses qauli and manhaji approaches. The qauli approach combines texts from fiqh books with texts from the Qur'an and Hadith. In contrast, the manhaji approach involves exploring the principles of fiqh and usul al-fiqh (manhajiy school) based on public interest considerations. Abstrak: Fatwa selama ini disusun oleh lembaga keagamaan di Indonesia. Tidak banyak lembaga pendidikan Islam yang berbasis pada pesantren melakukan istinbāṭ al-aḥkām dalam merespons persoalan-persoalan kontemporer. Ma’had Aly Salafiyah Syafi'iyah Sukorejo Situbondo Jawa Timur (Ma’had Aly Situbondo) merupakan salah satu lembaga pendidikan Islam di lingkungan pesantren yang berkontribusi pada penyusunan fatwa. Penelitian ini mengkaji istinbāṭ al-aḥkām yang dilakukan Ma’had Aly Situbondo dengan menggunakan metode field research yang digali dari wawancara kepada mahasiswa dan dosen Ma’had Aly Situbondo serta studi dokumen yang bersumber dari buletin Tanwirul Afkar tahun 2020-2021. Buletin tersebut berisi kumpulan hasil istinbāṭ al-aḥkām Ma’had Aly Situbondo dalam merespons problematika hukum kontemporer. Temuan penelitian menjelaskan bahwa istinbāṭ al-ahkām Ma’had Aly Situbondo dilakukan dengan pendekatan qawlī dan pendekatan manhajī. Pendekatan qawlī dilakukan dengan memadukan antara teks yang terdapat dalam kitab-kitab fikih dengan teks al-Qur’an dan hadis, sedangkan pendekatan manhajī dilakukan dengan menelusuri kaidah fikih dan ushul fikih yang berbasis pada kemaslahatan.